Toxoplasma gondii inhibits mast cell degranulation by suppressing phospholipase Cγ-mediated Ca2+ mobilization - Smith, Norah L.; Abi Abdallah, Delbert; Butcher, Barbara A.; Denkers, Eric; Baird, Barbara; Holowka, David (Frontiers in Microbiology, 2013)
Toxoplasma gondii is well known to subvert normal immune responses, however, mechanisms are incompletely understood. In particular, its capacity to alter receptor-activated Ca2+-mediated signaling processes has not been well-characterized. In initial experiments, we found evidence that T. gondii infection inhibits Ca2+ responses to fMetLeuPhe in murine macrophages. To further characterize the mechanism inhibition of Ca2+ mobilization by T. gondii, we used the well-studied RBL mast cell model to probe the capacity of T. gondii to modulate IgE receptor-activated signaling within the first hour of infection. Ca2+ mobilization that occurs via IgE/FcεRI signaling leads to granule exocytosis in mast cells. We found that T. gondii inhibits antigen-stimulated degranulation in infected cells in a strain-independent manner. Under these conditions, we found that cytoplasmic Ca2+ mobilization, particularly antigen-mediated Ca2+ release from intracellular stores, is significantly reduced. Furthermore, stimulation-dependent activation of Syk kinase leading to tyrosine phosphorylation and activation of phospholipase Cγ is inhibited by infection. Therefore, we conclude that inhibitory effects of infection are likely due to parasite-mediated inhibition of the tyrosine kinase signaling cascade that results in reduced hydrolysis of phosphatidylinositol 4,5-bisphosphate. Interestingly, inhibition of IgE/FcεRI signaling persists when tachyzoite invasion is arrested via cytochalasin D treatment, suggesting inhibition is mediated by a parasite-derived factor secreted into the cells during the invasion process. Our study provides direct evidence that immune subversion by T. gondii is initiated concurrently with invasion.